A Fuzzy Logic Approach to Decision Support in Medicine (Bangladesh Journal of Scientific and Industrial Research, 2011)
We established an application of fuzzy set logic for the development of a decision support in medicine. In this case, we apply a model on the prognosis of a patient suffering heart failure treated with beta-blockers. It shows how the basic rules are represented in a system depending on fuzzy logic based on expert experience. Keywords: Left ventricular diastolic diametre (LVDD); Dyspnea; Asthenia; Telediastolic; Ischemia; Servical vertibra three (S3); Atrio Venticular Block (AVB); Pace maker (PM); Heart failure probability (HFP). DOI: http://dx.doi.org/10.3329/bjsir.v46i1.8103 Bangladesh J. Sci. Ind. Res. 46(1), 41-46, 2011